2021
DOI: 10.1093/eurjpc/zwab208
|View full text |Cite
|
Sign up to set email alerts
|

Statin use and risk of dementia or Alzheimer’s disease: a systematic review and meta-analysis of observational studies

Abstract: Aims As the potential impact of statins on cognitive decline and dementia is still debated, we conducted a meta-analysis of observational studies to examine the effect of statin use on the risk of Alzheimer’s disease (AD) and dementia. Methods and results PubMed, Cochrane, and EMBASE were searched since inception to January 2021. Inclusion criteria were: (i) cohort or case–control studies; (ii) statin users compared to non-us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 91 publications
2
48
0
Order By: Relevance
“…In agreement, defects in brain cholesterol homeostasis can be linked to the prevalence of neurodegenerative diseases such AD, Parkinson’s disease, Niemann–Pick disease type C, and Huntington’s disease, among others [ 31 , 38 , 39 , 40 ]. Particularly, early studies in AD pathology described elevated levels of cholesterol in the brain of AD patients, which agrees with the epidemiological and observational studies in which statins, a cholesterol-lowering drug, seem to exhibit a positive effect against AD incidence [ 41 , 42 , 43 , 44 ]. Conversely, other works found a reduced content of cholesterol in several cortical areas of the human brain [ 45 ], but also in the hippocampus of SAMP8 mice [ 37 ].…”
Section: Discussionsupporting
confidence: 81%
“…In agreement, defects in brain cholesterol homeostasis can be linked to the prevalence of neurodegenerative diseases such AD, Parkinson’s disease, Niemann–Pick disease type C, and Huntington’s disease, among others [ 31 , 38 , 39 , 40 ]. Particularly, early studies in AD pathology described elevated levels of cholesterol in the brain of AD patients, which agrees with the epidemiological and observational studies in which statins, a cholesterol-lowering drug, seem to exhibit a positive effect against AD incidence [ 41 , 42 , 43 , 44 ]. Conversely, other works found a reduced content of cholesterol in several cortical areas of the human brain [ 45 ], but also in the hippocampus of SAMP8 mice [ 37 ].…”
Section: Discussionsupporting
confidence: 81%
“…Oral antidiabetics and insulin seem able to reduce cognitive impairment in AD [ 156 ]. Statin use is not associated with an increased risk of cognitive impairment, and some small observational studies seem to associate this treatment with a potentially favourable role in the setting of AD [ 157 ]. Long-term oxygen therapy, also, seems to improve cognition hypoxemic patients affected by AD [ 128 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…Atorvastatin is used to treat high cholesterol and triglyceride levels, shows potentially beneficial but not significant effects on AD in 27,28 . We observed that atorvastatin was associated with a 21% reduced risk of AD (HR 0.79, 95% CI 0.77-0.81) in OneFlorida and a 12% reduced risk of AD (HR 0.88, 95% CI 0.85-0.90) in MarketScan.…”
Section: Resultsmentioning
confidence: 99%